2002
DOI: 10.1002/sres.499
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the genealogy of systems thinking

Abstract: This paper illustrates a procedure for demonstrating and quantifying the importance of passivity in linear macromodels. This issue is critical whenever the macromodels are derived from tabulated port responses, either in time or frequency domain. We show an algorithmic procedure for the design of a passive termination network that will drive a given non‐passive macromodel to instability. Several termination structures characterized by various port couplings are investigated. Relaxed passivity conditions are al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 9 publications
0
42
0
4
Order By: Relevance
“…Therefore, many researchers have suggested that today's most vexing issues cannot be addressed using reductionist approaches (Capra, 1997;Hammond, 2002;Laszlo, 1996). Systems theory and its holistic approach is often suggested as an alternative that might be used to understand current situations and bringing about positive change (Adams et al, 2014;Hammond, 2002;von Bertalanffy, 1972). Our question becomes, 'how can we use systems theory to articulate pathologies as part complex system problem formulation?'…”
Section: Systems Theory-based Pathologiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, many researchers have suggested that today's most vexing issues cannot be addressed using reductionist approaches (Capra, 1997;Hammond, 2002;Laszlo, 1996). Systems theory and its holistic approach is often suggested as an alternative that might be used to understand current situations and bringing about positive change (Adams et al, 2014;Hammond, 2002;von Bertalanffy, 1972). Our question becomes, 'how can we use systems theory to articulate pathologies as part complex system problem formulation?'…”
Section: Systems Theory-based Pathologiesmentioning
confidence: 99%
“…Our question becomes, 'how can we use systems theory to articulate pathologies as part complex system problem formulation?' First, it is important to note that there is no one single common definition of systems theory (Adams et al, 2014;Hammond, 2002). However, ideas central to systems theory emerged in the 1940s and is commonly attributed to Anatol Rapoport, Norbert Weiner, Karl Ludwig von Bertalanffy and Ross Ashby as they attempted to provide an alternative approach to reductionism and provided a platform for uniting sciences (Laszlo, 1996;von Bertalanffy, 1950).…”
Section: Systems Theory-based Pathologiesmentioning
confidence: 99%
See 3 more Smart Citations